16S rDNA-Based Identification of Novel Superoxide Dismutase Producing Bacteria Isolated from Indonesia - ANA INDRAYATI; VALENTINA YURINA; LARAS AJENG PITAYU; DEBBIE SOEFIE RETNONINGRUM (Indonesian Society for microbiology, 2011)
Superoxide dismutase (SOD) has therapeutic importance because of its antioxidant activity and protects cells from reactive oxygen species attack. This research was intended to screen bacteria isolated from Indonesia for producing novel SODs and to identify the producers using 16S rDNA approach. Intracellular proteins were each extracted and assayed for their inhibition reduction activity by colorimetric method and by zymography for the presence of SOD protein band(s). For species identification, each of 16S rDNAgenes was amplified by polymerase chain reaction from genomicDNAfollowed by sequencing, BLAST, multiple alignment and phylogenetic analyses. All 16 intracellular proteins gave inhibition reduction percentage in the range of 15 to 70% and in zymography, their SOD profiles were quite diversed with at least one intenseSOD band present in most isolates. The SOD producers were assigned to three species, Flavobacterium okeanokoites, Escherichia fergunosii, and E. coli, and to four genera, Pantoea, Escherichia, Bacillus, and Pectobacterium. The remaining five were grouped in gamma-proteobacterium cluster and two formed a cluster with Pseudomonas. Three marine and four soil isolates could be attractive candidates for novel SODs based on unique properties of SOD producers. In conclusion, 16s rDNA-based identification of bacteria isolated from Indonesia reveals that seven isolates might be attractive candidates for novel SOD producers to be applied in pharmaceutical fields in the future.